PENGARUH FAKTOR BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN MANGGARAI - Subijanto; Woro Utari; Edelbertus Romo Ganggut (Pusat Riset dan Inovasi Nasional, 2021)
This research is an expalanotory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 35 people. The objectives of this study are 1). To analyze and analyze the influence of organizational culture and work discipline which have a significant effect on the performance of employees of the Manggarai Regency DPRD secretariat employees. 2) To test and analyze the influence of organizational culture and work discipline have a significant effect on employee performance in the secretariat staff of DPRD Manggarai Regency. 3) To see the variables that have a significant effect on the performance of employees of the Manggarai Regency DPRD secretariat employees. The results showed that: 1). Simultaneously, organizational culture and work discipline have a significant effect on employee performance at the Manggarai Regency DPRD Secretariat as evidenced by the result of the calculated F value of 3,348 with a significance value of 0.02 which means less than 0.05. 2). Partially, organizational culture and work discipline have a significant effect on employee performance at the Manggarai Regency DPRD secretariat. 3). Based on the test results, it is known that organizational culture affects the performance of employees at the Manggarai Regency DPRD secretariat; as evidenced by the t value is 5.583 with a significance level of 0.001 (less than 0.05). Keywords : Organizational Culture, Work Discipline and employee Performance